PENGEMBANGAN MATERI PENDIDIKAN AGAMA ISLAM BERBASIS KEBUTUHAN PESERTA DIDIK SEKOLAH DASAR - Hilmi Bayhaqi Hakim; Salwa Sofia Putri; Mohammad Nabil Musyafa' Ilham Pedrossa; Najwa Valerina Azzahra; Abdul Khobir; Nadya Kamilia (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study examines the development of Islamic Religious Education (IRE) materials based on the needs of elementary school students. The background of this study is the existence of IRE materials that are not fully aligned with students’ cognitive development, making learning less effective and less engaging. The purpose of this study is to explain the importance of developing IRE materials that are relevant to students’ characteristics so that learning becomes more meaningful. This research uses a qualitative method with a literature review approach by collecting data from books, scholarly journals, and articles related to learning material development and child development. The results show that IRE materials need to be developed by considering the principles of relevance, consistency and adequacy so that they are in line with learning objectives and students’ needs. Material that are contextual, attractive, and closely related to daily life can improve students’ understanding, participation, and character formation. Therefore, developing IRE materials based on students’ needs is essential to create effective, enjoyable learning and to support the formation of a generation that is faithful, morally noble, and ready to face future challenges.